PERANAN PEMERINTAH DAERAH DALAM MENINGKATKAN LITERASI MASYARAKAT DI PROVINSI BANTEN - Ilham Suhadhan; Tito Inneka Widyawati; Achmad Chumeidi; Fitria Santi (Halu Oleo University, 2023)
This study highlights the strategies used by the local government in Provincia Banten to increase the level of literacy among the populace. The present study employs a qualitative method of inquiry and relies on a single source of information. The focus of the study is the Pemerintah Theory of the Four Regions as outlined by Arif (2012): (1) Regulator, (2) Facilitator, (3) Dinamisator, and (4) Katalitator. In this study, observation, in-depth interviews, and documentation were used to collect data. This study uses the method of collecting data, reducing data, displaying data, and drawing conclusions. This study shows that the role of local governments in using various programs, both directly and indirectly, such as social media platforms, is not ideal. This is due to the lack or limitations of the facilities and infrastructure that are already owned by the local government, the lack of infrastructure to reach the area, the lack of public understanding of the use of information technology, the lack of internet network access, and the lack of resources at the Regional Library and Archives Service of Banten Province